Determinants of Regional Government Financial Performance in Central Sulawesi Province - Fajar Dakhilulloh; Dewi Salmita; Muhammad Syafaat; Moh. Agus Nugroho (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Regional autonomy is designed to enhance the efficiency of governance and the quality of public services through the delegation of greater authority to local governments. In this context, financial performance serves as a key indicator in assessing the success of autonomy implementation. This study aims to analyze the effect of financial dependence, financial independence and the effectiveness of local own-source revenue both partially and simultaneously on the financial performance of regencies/cities in Central Sulawesi Province for the period 2018–2023. A quantitative approach with a descriptive-causal design was employed. The sample consisted of 13 regencies/cities selected using a saturated sampling technique. Data were obtained from the audited Local Government Financial Reports (LKPD) issued by the Audit Board of Indonesia (BPK) for the period 2018–2023, resulting in a total of 78 observations. The data analysis is conducted using panel data regression, assisted by Eviews 12 software. The results indicate that the three variables simultaneously have a significant effect on regional financial performance. Partially, financial dependence and financial independence have a significant effect on regional financial performance, whereas the effectiveness of local own-source revenue does not show a significant effect. These findings contribute to regional fiscal policy making by highlighting the importance of enhancing financial management strategies, particularly in reducing dependence on central government transfers and strengthening financial independence. Efforts such as optimizing local own-source revenue and improving public spending efficiency should be prioritized to enhance regional financial performance.